Snake and Ladder Game Integrated with Asmaul-husna: Development of Learning Media. (February 2019) - Meriyati; Latifah, S; Hidayah, N; Shawmi, A N; Amrullah, M. A; Fitriana, N S
Abstract: This study aims to determine the attractiveness, feasibility, and response of students in using snake ladder game media integrated with asmaul husna on the theme of animal and human movement organs. The development research method adapted to the Borg and Gall model using seven steps: potential problems, data collection, product design, product validation, product revision, product trials, and product revision. Data collection tools used is the material expert questionnaire, media expert questionnaire and educator response questionnaire to determine product feasibility, and questionnaire responses of students to find out the attractiveness of the product. The results of the research that have been developed obtain a percentage of the feasibility of 92% by material experts, 90% by media experts, and 89% by educators. The percentage of participants' responses to product attractiveness gained 92%. Based on the results of the description above, the products developed by researchers are suitable for use as learning media.